Case Report: Thelotomy in a Dairy Buffalo after Ultrasonographic Diagnosis of Teat Stenosis - Shokry, Mohamed Mostafa; Berbish, Elsayed Ashor (Journal of Buffalo Science, 2012)
Teat cistern stenosis was surgically treated by thelotomy and excision of the fibrous stenosis following teat ultrasonography to determine location and extent of the lesion in a dairy water buffalo.